Quality in Higher Education and Satisfaction among Professors and Students - María del Carmen Olmos-Gómez; Mónica Luque-Suárez; Concetta Ferrara; Jesús Manuel Cuevas-Rincón (MDPI AG, 2021)
The aim of this study was to analyze the significant differences in satisfaction with educational quality in higher education in Italy (Naples) among students and professors. The sample consisted of 501 higher education students and 121 professors, resulting in a total sample size of 622 subjects. Once the quality parameters of the instrument were determined, reliability was confirmed, and data collection was initiated. In order to analyze the results, a test of independent means (Student's t-test) was performed, interrelating the variables of educational quality, concerning both management and satisfaction with higher education. Based on the results, we concluded that there are significant differences between the group of students and the group of professors, highlighting a higher level of satisfaction with quality reported by students regarding the coordination of teachers and staff in the educational process; therefore, the inclusion of students in the direct management of the center should be more active and an indicator to be taken into account in self-evaluation. Despite the limitations in the sample at the regional level, it offers many possibilities for future research.